Removing of resins from crude oils. (17th April 2016) - Demirbas, Ayhan; Taylan, Osman
ABSTRACT: Crude oil contains four chemical group classes, namely saturates, aromatics, resins, and asphaltenes (SARA fractions). Resins fraction of crude oil comprises polar molecules often containing heteroatoms such as nitrogen, oxygen, or sulfur. Resin is a heavier fraction than aromatics and saturates. Resins are composed of fused aromatic rings with branched paraffin and polar compounds. The resin fraction is soluble in light alkanes such as pentane and heptane, but insoluble in liquid propane. The resins are adsorbed on a solid such as alumina, clay, or silica, and subsequently recovered by use of a more polar solvent and the oils (aromatics and saturates) remain in solution. The resins often coprecipitate with the asphaltenes in controlled propane deasphalting procedures. The composition of the resins can vary considerably and is dependent on the kind of precipitating liquid and on the temperature of the liquid system. The resins are adsorbed on a solid such as alumina, clay, or silica, and subsequently recovered by use of a more polar solvent and the oils (aromatics and saturates) remain in solution.